Research on Integrated Design of Modular Steel Structure Container Buildings Based on BIM - Meng Su; Bauer Yang; Xiaomin Wang (Advances in Civil Engineering)
Modular container buildings, as new modular steel structure buildings with the advantages of modular construction and transportation, fast construction speed, and conformance to the concept of sustainable development, have achieved rapid development in the field of civil engineering in recent years. However, in view of the incompatibility of the standards and systems between the traditional construction industry and the container manufacturing industry, contradictions between industrialization, standardization requirements and diversified demands of buildings, and the low integration of the design system of modular steel structure buildings, the further development of the modular container building industry has encountered a bottleneck. In this study, for resolving this problem, it was proposed to coordinate the modular sequence of the construction and container manufacturing, establish a modular system for modular steel structure buildings, establish a database of container building components and parts, and integrate BIM and PDM platforms, to strengthen professional coordination and improve the integrated design that can increase the integration of the whole process of design. The application and verification in pilot projects such as Huaduhui Commercial Street have approved that this design method can effectively improve the standardization, industrialization, and information levels of design, production, and construction, increase the diversity and overall quality of modular buildings, and promote the achievement of the integration target of the modular steel structure building system.